DISTRIBUSI UDANG PENAEUS SP DI PERAIRAN PANT AI TELUK SEMARANG - Galih Rasiono (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2005)
Penaeus spare of the most valuable marine resources at Semarang gulf'howerer, information it is very limited. This research try to find out the information dealing with its managemen. The data collecting method of this research is surveyusing sample. Peneaus sp, were caught as the samples, collected from the 3 location. Each location consist of 4 depthse about 1 m, 5 m, 10 m and 15 m. Using push net in the depth about I m and Beam Trawl ( Cotok ) in the depth of 5 m, 1O m, 15 m. The results show that the composition of Penaeus sp consists of P. merguiensis, P. indicus, P. semisulcatus and P. monodon. The size of Penaeus sp caught were 2, 7 - 15,0 cm, but most of them dominated by the small size ( Less than 8 cm).